2015
DOI: 10.1039/c5fo00469a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the antiadipogenic-antiobesity effects of a rice hull smoke extract in 3T3-L1 preadipocyte cells and in mice on a high-fat diet

Abstract: The present study investigated the inhibitory effects of a rice hull smoke extract (RHSE) against adipogenesis in 3T3-L1 preadipocyte cells and in mice fed high fat (HFD) and normal (ND) diets. At concentrations of 0.1% and 0.5%, RHSE was shown to reduce the cellular lipid content in MDI-induced 3T3-L1 cells by about 72% and 88%, respectively, compared to that in control cells without RHSE, indicating a strong antiadipogenic effect. This result was supported by the finding that the expression of the adipocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…We are also engaged in a parallel effort designed to define the potential health benefits of antioxidative fruits and vegetable peels, as well the peel (hull) from rice, which are often discarded as a food-processing waste product [9,10,11]. As part of this effort, we have shown that (a) the dietary supplementation of potato peel powders reduced weight gain in mice on a high-fat diet [12]; (b) potato peel powders inhibited the growth of pathogenic trichomonads (protozoa) that cause sexually transmitted diseases in humans and cattle [13]; (c) apple, orange, and potato peel powders inhibited the outgrowth of pathogenic Bacillus cereus bacteria from spores in cooked rice [14]; and (d) a rice hull smoke extract reduced weight gain in mice on a high-fat diet [15]. We also recently determined the content of phenolic and flavonoid compounds and antioxidative activities of 12 melon peel powders [16].…”
Section: Introductionmentioning
confidence: 99%
“…We are also engaged in a parallel effort designed to define the potential health benefits of antioxidative fruits and vegetable peels, as well the peel (hull) from rice, which are often discarded as a food-processing waste product [9,10,11]. As part of this effort, we have shown that (a) the dietary supplementation of potato peel powders reduced weight gain in mice on a high-fat diet [12]; (b) potato peel powders inhibited the growth of pathogenic trichomonads (protozoa) that cause sexually transmitted diseases in humans and cattle [13]; (c) apple, orange, and potato peel powders inhibited the outgrowth of pathogenic Bacillus cereus bacteria from spores in cooked rice [14]; and (d) a rice hull smoke extract reduced weight gain in mice on a high-fat diet [15]. We also recently determined the content of phenolic and flavonoid compounds and antioxidative activities of 12 melon peel powders [16].…”
Section: Introductionmentioning
confidence: 99%
“…The time at which HFD-fed mice develop decreased serum or plasma adiponectin concentrations varies in the literature. Some studies, using a range of diets that contain anywhere from 40% to 60% lard, demonstrate decreased adiponectin concentrations by as early as 4 weeks on the diet [ 50 , 51 , 52 ]. However, another study similar to ours did not observe an HFD-mediated decrease in adiponectin after 10 weeks on an HFD that consisted of 60% lard [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed using the MTT staining assay following the method of Mosmann [26]. This method has previously been applied to 3T3-L1 cells [27, 28]. Briefly, cells were treated with serial concentrations of purpurin (0, 1, 10, 50, 100, 250 μM) for 24 h or 48 h at 37 °C in humidified air with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were induced to differentiate according to methods used previously [27, 28]. Briefly, 3T3-L1 murine pre-adipocyte cells were stimulated to differentiate by culturing in MDI medium in the presence and absence of purpurin for 2 days.…”
Section: Methodsmentioning
confidence: 99%